2019
DOI: 10.1186/s13054-019-2465-y
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy versus conventional oxygen therapy in patients after planned extubation: a systematic review and meta-analysis

Abstract: Background The effect of high-flow nasal cannula (HFNC) therapy in patients after planned extubation remains inconclusive. We aimed to perform a rigorous and comprehensive systematic meta-analysis to robustly quantify the benefits of HFNC for patients after planned extubation by investigating postextubation respiratory failure and other outcomes. Method We searched MEDLINE, EMBASE, Web of Science, and the Cochrane Library from inception to August 2018. Two researchers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 39 publications
3
51
2
4
Order By: Relevance
“…HFNC is a novel oxygen therapy developed in recent years, in which oxygen at a certain concentration mixed with highflow gas is directly delivered to patients through a nonsealed nasal cannula [6,7]. is oxygen therapy has been assessed by many studies and can be applied to patients with acute hypoxemic respiratory failure, status-post surgery, and respiratory failure without tracheal intubation, immunosuppression, and cardiac insufficiency, thus effectively improving oxygenation [8][9][10][11][12][13][14][15]. However, few studies have confirmed the efficacy of HFNC in treating bronchial asthma, focusing mainly on pediatric and neonatal patients [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…HFNC is a novel oxygen therapy developed in recent years, in which oxygen at a certain concentration mixed with highflow gas is directly delivered to patients through a nonsealed nasal cannula [6,7]. is oxygen therapy has been assessed by many studies and can be applied to patients with acute hypoxemic respiratory failure, status-post surgery, and respiratory failure without tracheal intubation, immunosuppression, and cardiac insufficiency, thus effectively improving oxygenation [8][9][10][11][12][13][14][15]. However, few studies have confirmed the efficacy of HFNC in treating bronchial asthma, focusing mainly on pediatric and neonatal patients [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ HFNC was initially utilized as an alternative breathing support for premature infants to maintain positive airway pressure [37][38][39] ; however, there is a propensity to use HFNC therapy in adults with respiratory distress 8,40,41 . In the latest meta-analysis conducted by Zhu and colleague 40 , HFNC had significantly effect on reducing post-extubation respiratory failure rate, respiratory rates, and increasing PaO 2 , comparing with conventional oxygen therapy in patients after planned extubation. In most of studies [42][43][44] , HFNC was compared with standard of care to demonstrate that this approach was able to improve oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…
We read with great interest the recent systematic review and meta-analysis of high-flow nasal cannula (HFNC) oxygen therapy versus conventional oxygen therapy (COT) in patients after planned extubation [1]. We greatly appreciate Zhu Y and colleagues' efforts, but some important issues may better be discussed.First, randomized controlled trials (RCTs) and non-RCTs may be inappropriately combined together in the meta-analysis, which goes against the principle of pooling studies with the similar design [2, 3].
…”
mentioning
confidence: 99%
“…Therefore, the figure of trial sequential analysis may better be not drawn based on a rough estimated RRR. Thank you very much for giving us the opportunity to respond to the valuable comments pointed out by Meng-Si Luo and colleagues with regard to our study [1].First, randomized controlled trials (RCTs) and crossover studies were not pooled together for primary outcome and main secondary outcomes in our article, only pooled together for secondary outcomes of respiratory rate, PaO 2 , and comfort score. According to the guidelines described in the Cochrane Handbook for Systematic Reviews of Interventions, quasi-RCTs and cross-over studies can be included for analysis, particularly when few RCTs addressing the topic of the review are identified [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation